Aggregate and Idiosyncratic Risk in a Frictional Labor Market - Rudanko, Leena (American Economic Review, 2011)
This paper develops a tractable extension of a Mortensen-Pissarides style matching model that allows for risk averse workers with limited ability to smooth consumption. I show that this leads to a form of equilibrium wage rigidity, as the inability of workers to smooth their consumption across unemployment and employment spells changes how unemployed workers value wage offers, and hence also the offers that employers find profitable to make. In the model risk-averse entrepreneurs use optimal long-term contracts to attract risk averse workers facing limited access to asset markets. A simple analytic representation for the equilibrium is derived. JEL: D81, E21, E24, E32, J31, J41, J64